ANALISIS FAKTOR YANG MEMPENGARUHI ALIH FUNGSI LAHAN KARET MENJADI LAHAN SAWIT PADA ANGGOTA KUD LANGGENG KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI - Miming Novita Sari Novita Sari; Sri Kartikowati Kartikowati; Henny Indrawati Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The study aims to determine factors that influence rubber land conversion into palm oil plantation .The population in this research is the whole farmers whose rubber plantation have conservated into palm oil plantation in the village of Kuantan Sako Kecamatan Kuantan Sako. Sampling is taken by purposive sampling techigue. Data is collected through interview and observation. Data is analized then using descriptive analysis. The research found that there is influence factors to land convertion from rubber plantation into palm plantations, namely: economic, environmental, and technical aspects. It is adviced to government to pay attention the expantion of palm oil plantation accordance with te spatial area that has set the government, to avoid global warming. Keywords: Economic, environmental, technical.